2017
DOI: 10.3390/molecules22040669
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds and Digestive Enzymes: In Vitro Non-Covalent Interactions

Abstract: The digestive enzymes–polyphenolic compounds (PCs) interactions behind the inhibition of these enzymes have not been completely studied. The existing studies have mainly analyzed polyphenolic extracts and reported inhibition percentages of catalytic activities determined by UV-Vis spectroscopy techniques. Recently, pure PCs and new methods such as isothermal titration calorimetry and circular dichroism have been applied to describe these interactions. The present review focuses on PCs structural characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 110 publications
3
123
1
2
Order By: Relevance
“…In contrast to other digestive enzymes, such as pancreatic α‐amylase, pancreatic lipase and α‐glucosidase, effect of polyphenol compounds on digestive protease activity have been barely studied (Martinez‐Gonzalez and others ). Li and others () investigated the effect of different number of hydroxyl groups in four flavonoids, quercetin, luteolin, kaempferol and apigenin, on their inhibition of trypsin activity.…”
Section: Health Effects Of Plant Phenolic Compoundsmentioning
confidence: 99%
“…In contrast to other digestive enzymes, such as pancreatic α‐amylase, pancreatic lipase and α‐glucosidase, effect of polyphenol compounds on digestive protease activity have been barely studied (Martinez‐Gonzalez and others ). Li and others () investigated the effect of different number of hydroxyl groups in four flavonoids, quercetin, luteolin, kaempferol and apigenin, on their inhibition of trypsin activity.…”
Section: Health Effects Of Plant Phenolic Compoundsmentioning
confidence: 99%
“…Molecular interactions between digestive enzymes and phenolic compounds are mostly by van der Waals forces, hydrogen binding, hydrophobic binding, and other electrostatic forces. These interactions were previously associated to noncompetitive type inhibitions (Li, Yang, Fei, Zhang, & Wu, ; Martinez‐Gonzalez et al, ; Shobana, Sreerama, & Malleshi, ; Wang, Dong, Zhang, Shao, & Liu, ; Wu et al, ; Yang & Kong, ). Wang et al () reported that grape proanthocyanidins inhibited porcine pancreatic lipase activity in a noncompetitively inhibiting manner.…”
Section: Resultsmentioning
confidence: 80%
“…epigallocatechin) lower cholesterol level by inhibiting pancreatic lipase (Juhel et al, ). The efficacy of quercetin‐3‐xyloside and quercetin‐3‐glucoside in inhibiting the catalytic activity of PL was reported in the literature (Martinez‐Gonzalez et al, ). The dihydroflavonol derivatives, viz.…”
Section: Discussionmentioning
confidence: 93%